2022
DOI: 10.1002/naaq.10221
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Characterization of Inosine Monophosphate Delivered by a Nanoparticle in Rainbow Trout

Abstract: Rainbow Trout Oncorhynchus mykiss are a commonly farmed fish worldwide and, as such, are of economic importance in many countries. Inosine monophosphate (IMP) has been shown to have a positive effect on Rainbow Trout growth performance and overall health. The aim of the current study was to test whether a novel phytoglycogen nanoparticle (NP) was nontoxic and if it could enhance the positive effects of IMP on Rainbow Trout health at the cellular and whole-animal level. The NP used in this study is derived from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In fact, nanoparticles of various compositions have shown promise as carriers of poly inosinic: poly cytidylic acid (pIC), a commercially available viral dsRNA mimic, while effectively stimulating the immune system ( Kim et al, 2017 ; Sokolova et al, 2017 ; Gondan et al, 2018 ). Because nanoparticles of inorganic composition can have negative impacts on cells and their responses ( Jeng and Swanson, 2006 ; Villeret et al, 2018 ; Báez et al, 2021 ; reviewed by Sengul and Asmatulu, 2020 ), optimization with an organic nanoparticle, such as the phytoglycogen nanoparticle (NDX) previously used by our group ( Alkie et al, 2019 ; Jenik et al, 2021a ; Jenik et al, 2021b ), would be ideal. Previous work has shown that this phytoglycogen nanoparticle is non-toxic, can effectively deliver pIC to vertebrate cells, and can successfully limit rhabdovirus replication ( Alkie et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, nanoparticles of various compositions have shown promise as carriers of poly inosinic: poly cytidylic acid (pIC), a commercially available viral dsRNA mimic, while effectively stimulating the immune system ( Kim et al, 2017 ; Sokolova et al, 2017 ; Gondan et al, 2018 ). Because nanoparticles of inorganic composition can have negative impacts on cells and their responses ( Jeng and Swanson, 2006 ; Villeret et al, 2018 ; Báez et al, 2021 ; reviewed by Sengul and Asmatulu, 2020 ), optimization with an organic nanoparticle, such as the phytoglycogen nanoparticle (NDX) previously used by our group ( Alkie et al, 2019 ; Jenik et al, 2021a ; Jenik et al, 2021b ), would be ideal. Previous work has shown that this phytoglycogen nanoparticle is non-toxic, can effectively deliver pIC to vertebrate cells, and can successfully limit rhabdovirus replication ( Alkie et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%